Toxicity of Nanoparticulate Nickel to Aquatic Organisms: Review and Recommendations for Improvement of Toxicity Tests. (25th August 2020) - Meyer, Joseph S.; Lyons‐Darden, Tara; Garman, Emily R.; Middleton, Elizabeth T.; Schlekat, Christian E.
Abstract: We reviewed the literature on toxicity of nanoparticulate nickel (nano‐Ni) to aquatic organisms, from the perspective of relevance and reliability in a regulatory framework. Our main findings were 1) much of the published nano‐Ni toxicity data is of low or medium quality in terms of reporting key physical–chemical properties, methodologies, and results, compared with published dissolved nickel studies; and 2) based on the available information, some common findings about nanoparticle (NP) toxicity are not supported for nano‐Ni. First, we concluded that nanoparticulate elemental nickel and nickel oxide, which differ in chemical composition, generally did not differ in their toxicity. Second, there is no evidence that the toxicity of nano‐Ni increases as the size of the NPs decreases. Third, for most organisms tested, nano‐Ni was not more toxic on a mass‐concentration basis than dissolved Ni. Fourth, there is conflicting evidence about whether the toxicity is directly caused by the NPs or by the dissolved fraction released from the NPs. However, no evidence suggests that any of the molecular, physiological, and structural mechanisms of nano‐Ni toxicity differ from the general pattern for many metal‐based nanomaterials, wherein oxidative stress underlies the observed effects. Physical–chemical factors in the design and conduct of nano‐Ni toxicity tests are important, but often they are not adequately reported (e.g., characteristics of dry nano‐Ni particles and of wetted particles in exposure waters; exposure‐water chemistry). Environ Toxicol Chem 2020;39:1861–1883 © 2020 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.